Improving networked music performance systems using application‐network collaboration. (4th September 2018) - Lakiotakis, Emmanouil; Liaskos, Christos; Dimitropoulos, Xenofontas
Summary: Networked Music Performance (NMP) systems involve musicians located in different places who perform music while staying synchronized via the Internet. The maximum end‐to‐end delay in NMP applications is called Ensemble Performance Threshold (EPT) and should be less than 25 milliseconds. Due to this constraint, NMPs require ultra–low‐delay solutions for audio coding, network transmission, relaying, and decoding, each one a challenging task on its own. There are two directions for study in the related work referring to the NMP systems. From the audio perspective, researchers experiment on low‐delay encoders and transmission patterns, aiming to reduce the processing delay of the audio transmission, but they ignore the network performance. On the other hand, network‐oriented researchers try to reduce the network delay, which contributes to reduced end‐to‐end delay. In our proposed approach, we introduce an integration of dynamic audio and network configuration to satisfy the EPT constraint. The basic idea is that, the major components participating in an NMP system, the application and the network interact during the live music performance. As the network delay increases, the network tries to equalize it by modifying the routing behavior using Software‐Defined Networking principles. If the network delay exceeds a maximum affordable threshold, the network reacts by informing the application to change the audio processing pattern to overcome the delay increase, resulting in below EPT end‐to‐end delay. A full prototype of the proposed system was implemented and extensively evaluated in an emulated environment.